Vascular Plants of Makok Mountain in (Mountain Region-Rowanduz District) Kurdistan Region/Iraq. - Sdiq W. Mrad; Jawhar F. Saeed (Zanco Journal of Pure and Applied Sciences, 2023)
A study was conducted on the first comprehensive survey of vascular plants in the Makok Mountain. Surveyed Area located on the northwest of Sulaymaniyah governorate Iraqi Kurdistan Region, in the botanical physiographic mountain Rowanduz district, as a part of the mountain forest region. Surveyed area is situated about 120 km North of Sulaymaniyah city. The period of Field work were conducted from spring 2021 to spring 2022. Over 2000 plant taxa were collected. As a results, 351 plant taxa from 65 families and 243 genera were determined and identified. The 5 largest families in this study area such as Asteraceae (50 taxa: 32.05 %), Fabaceae (35 taxa: 22.44 %), Lamiaceae (28 taxa: 17.95 %), Poaceae (23 taxa: 14.74%), and Apiaceae (20 taxa: 12.82 %).